Pemanfaatan dan Strategi Pemasaran Olahan Tanaman Bambu - Ludvianto, Meganusa (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
This journal was created to fulfill the requirements for completing Kuliah Kerja Nyata ke 79 (KKN) activity that was carried out by Atma Jaya Yogyakarta University in 2021. The location that was used as the object of KKN for the writing team was Serut village which is in Gedangsari sub-district, Gunungkidul district. , the province of the Special Region of Yogyakarta. The theme raised by the writing team was the potential of Serut village. The writing team searched for data and information about Serut village via the internet by analyzing it through the official Serut village website and other related websites, and several related journals. The writing team found that Serut village's potential is the potential for a tourism village and the potential for natural resources, specifically the producer of Jati wood and bamboo wood. This program is expected to be able to help Serut villagers to be able to further develop the potential of their village.